Stability and Evolution of Fallen Particles Around the Surface of Asteroid (101955) Bennu - Amarante, A. [UNESP]; Winter, O. C. [UNESP]; Sfair, R. [UNESP] (Amer Geophysical Union, 2021)
In this study, we study the dynamics of particles around Bennu. The goal is to understand the stability, evolution, and final outcome of the simulated particles around the asteroid. According to the results, the particle sizes can be divided into two main groups depending on their behavior. Particles smaller than a centimeter are quickly removed from the system by solar radiation pressure, while the dynamics of particles larger than a few centimeters is dominated by the gravitational field of Bennu. Because of its shape and spin period, Bennu has eight equilibrium points around it. The structure of the phase space near its equatorial surface is directly connected to these equilibrium points. Therefore, we performed numerical simulations to obtain information about the orbital evolution near the equilibrium points. The results show that most of the particles larger than a few centimeters fall in the equatorial region close to the Kingfisher area or close to the region diametrically opposite to it. In contrast, almost none of these particles fall in the equatorial region close to the Osprey area. In addition, we also performed computational experiments considering a spherical cloud of particles initially orbiting Bennu. Most of the particles in prograde orbits fall on the surface within our integration period, which was limited to 1.14 years. The particles preferentially fall near high-altitude regions at low equatorial latitudes and close to the north pole. The mid-latitudes are those more depleted of falls, as in the Nightingale and Sandpiper areas. Plain Language Summary In general, asteroids are small bodies with a very irregular shape that is not spherical. Bennu is an asteroid being explored by the spacecraft mission OSIRIS-REx. This asteroid has a size smaller than 500 m (1/3 mile), and its shape is a bouldery spheroid with an equatorial ridge. Bennu's gravity is very weak and complicated because of its shape, and it rotates around itself about every 4 h. The evolution of the trajectories of small boulders around Bennu is a puzzling problem that is explored in this study. Performing computational simulations, we identified equilibrium positions and the preferred paths. Particles smaller than a centimeter are quickly removed from the system, while most particles of a few centimeters or larger collide with the surface of Bennu. The majority of the impacts are in the equatorial region where the locations near valleys of the surface did not have a significant number of falls, while the number of falls is high near peaks. The polar regions also show a considerable number of impacts, and there is a location in Bennu's north pole with a large number of falls. Last, this study presents animated movies showing the simulations. Key Points Key The dynamics of particles orbiting near the equator of Bennu are dominated by eight equilibrium points irregularly located around the asteroid Particles smaller than a centimeter are quickly removed from the system by the solar radiation pressure Particles larger than a few centimeters, initially orbiting in a spherical cloud around Bennu, preferentially fall onto the surface near high-altitude regions at low equatorial latitudes and close to the north pole